SPATIAL VARIABILITY OF THE HEAT EMITTED FROM THE LAND SURFACE IN DETERMINING THE CHARACTERISTICS OF DESERT SOILS IN AL-SAMAWAH DESERT USING “GIS” - A. A. Akram; A. I. Hamad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to reveal the variation land surface temperature "LST" with some characteristics of desert soils in the Samawa desert at Al-Muthanna province, and to adopt solutions and treatments by identifying factors and indicators that have a direct impact to desertification, by using geographic information systems mapping for spatial distribution Some physical and chemical properties were selected. . the result showed that there was a statistical relationship between LST and the physical characteristics, as it was revealed that the comparison of sand and silt content with the land surface temperature "LST" . There is a significant relationship with the determination coefficient of R2=0.6. The chemical properties, the results showed that there was a significant connection between the electrical conductivity with the land surface temperature with a coefficient of determination R2=0.5 and an It was also observed that there is a significant relationship between the land surface temperature and the temperature measured in the field with a determination coefficient R2=0.6.